Determinants of Purchase Intention in Plant-Based Seafood Products among Generation Z in Malaysia - Hoo, Wong Chee; Madhavedi, Sudhakar; Yi, Tiong Chin; Hossain, Syed Far Abid; Prompanyo, Manoch (Journal of Ecohumanism, 2024)
The increasing apprehensions regarding the depletion of marine life and exploitation in Malaysia have prompted the proposal of plant-based aquaculture as a prospective resolution. In order to successfully penetrate the Malaysian market with plant-based seafood, it is imperative to conduct an in-depth examination of the factors that influence consumers’ purchasing intentions. The aim of this research endeavour is to examine the factors that influence the intention of Generation Z consumers in Malaysia to buy plant-based seafood. By employing the theory of planned behaviour (TPB) as a conceptual framework, this research achieved its objective and examined the impacts of five discrete independent variables namely, attitude, subjective norms, perceived behavioural control, food safety, and environmental concern on one another. In Malaysia, 384 online surveys completed by members of Generation Z were compiled for this investigation. The Statistical Package for the Social Sciences (SPSS) was utilised in this investigation. The findings suggest that purchase intent is significantly influenced by factors such as attitude, perceived behavioural control, food safety, and environmental concern, as opposed to subjective norms. The findings of the multiple regression analysis indicate that purchase intent cannot be predicted by every single one of the independent variables examined in this article.